Initial Chest X-ray scoring in the prediction of COVID-19 patients’ outcome in the United Arab Emirates - Ibrahim, Saabh; Albadra, Mustafa; Tadros, Fady (Journal of the Faculty of Medicine Baghdad, 2022)
Background: The radiological scoring of severity and progression of lung abnormalities is of great value for clinicians to define the clinical management of COVID-19 patients.Objectives: The purpose of this study is to implement the Brixia scoring tool to assess the pattern of lung involvement in patients with COVID-19 to help predict the severity of their clinical outcome, where the clinical outcome correlates to outpatient, inpatient and/or ICU admission.Patients and Methods: We conducted a case series study at the Sheikh Khalifa Medical City Ajman (SKMCA), United Arab Emirates from 14 March to 30 October 2020. Patients’ medical records were reviewed and followed up from the time of diagnosis until discharge and/or death. The patients were included based on the following criteria: Confirmed COVID-19 infection via RT-PCR assay, symptoms of COVID-19 within one week prior to presenting at the hospital and an initial Chest X-ray at hospital presentation. Two independent and experienced radiologists implemented the Brixia scoring tool for the assessment of pulmonary involvement detected on CXR of patients with COVID-19.Results: We reported cut-off values of the CXR score to be 7 for ICU admission (sensitivity=84.1%) and a cut-off score of 9 to predict the outcome of death (sensitivity=70.4%); where both values were statistically significant with p-value